Sanksi Bagi Pelaku Ojek Online Yang Melakukan Order Fiktif Menggunakan Aplikasi “Fiktif” - Nur Muhammad Wildanu; Yuswalina; Dodi Irawan (Journal of Sharia and Legal Science, 2023)
Advances in transportation at this time is the existence of online transportation. This provides convenience to the community. However, this is also used by people who want to get benefits in the wrong way, such as placing fictitious orders. Therefore, this paper examines the sanctions for the perpetrators of these fictitious orders, both in positive law and Islamic criminal law. The type of data in this study is a type of library research (library research) while the data analysis technique is a normative juridical method, namely compiling systematically, connecting one another related to the problems studied with the enactment of laws and regulations. The results of this study concluded that the sanctions against online motorcycle taxi drivers who make fictitious orders using fictitious applications are in accordance with Law No. 19 of 2016 concerning Electronic and Transaction Information, namely imprisonment for a maximum of 8 (eight) years in prison and a maximum fine of Rp. 800,000,000 (eight hundred million rupiah) and in Article 378 of the Criminal Code it is included in fraud and is subject to imprisonment for a maximum of 4 (four) years. According to Islamic criminal law, online motorcycle taxi drivers who make fictitious orders using this fictitious application are subject to ta'zir punishment, namely punishments that have not been determined either in the Qur'an or hadith. Because the punishment is to create a deterrent effect so as not to repeat it. This act is an act of fraud.